2021
DOI: 10.34172/japid.2021.004
|View full text |Cite
|
Sign up to set email alerts
|

Different techniques in transalveolar maxillary sinus elevation: A literature review

Abstract: Dental implant treatment in the posterior maxilla encounters bone quality and quantity problems. Sinus elevation is a predictable technique to overcome height deficiency in this area. Transalveolar sinus elevation is a technique that is less invasive and less time-consuming, first introduced for ridges with at least 5 mm of bone height. Many modifications and innovative equipment have been introduced for this technique. This review aimed to explain the modifications of this technique with their indications and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(82 reference statements)
0
11
0
1
Order By: Relevance
“…Sinus lifting techniques has been improved all over the years, starting with lateral approach, followed by transcrestal approach and its modifications. Summers was the first to describe transcrestal approach in 1994, several techniques were used in addition to osteotome (18), until 2016 when Hauwis and Meyer introduced the densah burs and introduced using it in sinus lifting (13). In the current study, we compared the effect of densah burs versus osteotome in transcrestal maxillary sinus lifting in 12 patients.…”
Section: Discussionmentioning
confidence: 97%
“…Sinus lifting techniques has been improved all over the years, starting with lateral approach, followed by transcrestal approach and its modifications. Summers was the first to describe transcrestal approach in 1994, several techniques were used in addition to osteotome (18), until 2016 when Hauwis and Meyer introduced the densah burs and introduced using it in sinus lifting (13). In the current study, we compared the effect of densah burs versus osteotome in transcrestal maxillary sinus lifting in 12 patients.…”
Section: Discussionmentioning
confidence: 97%
“…It is becoming more common to repair vertically resorbed ridges before implant placement to optimize implant fixation and future osseointegration (7,8). To ensure a successful implant therapy, various sinus floor lift techniques have been tried to increase the availability of bone in this location (9). Tantun (10) proposed the procedure in 1976, which involved surgical access gained to the sinus by entering the lateral wall of the maxillary zygomatic buttress followed by insertion of bone grafting substance (10).…”
Section: Introductionmentioning
confidence: 99%
“…The membrane is gently detached with a latex balloon inflated with saline solution and inserted via a hole through the lateral wall of the sinus. In 2006, Kfir et al, (18) demonstrated a crestal sinus elevation utilizing the inflating balloon procedure, with placement of dental implants and bone grafts simultaneously in the same surgical step (9). It is, nonetheless, technically challenging, and costeffective.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations